Convergent Validity of Two Sensory Questionnaires in Spain: Sensory Profile-2 and Sensory Processing Measure - Berta Gándara-Gafo; Isabelle Beaudry-Bellefeuille (MDPI AG, 2023)
(1) Background: Several sensory questionnaires aimed at analyzing sensory reactivity problems in children are available in Spain; however, knowledge about whether these questionnaires can obtain equivalent results is lacking. The purpose of this study was to examine the convergent validity of two sensory questionnaires available for the Spanish population (Spain): Sensory Profile-2 (SP-2) and Sensory Processing Measure (SPM). (2) Methods: This study involved a sample of 116 children between the ages of 5 and 12 years with sensory integration differences and concerns with participation in daily activities. A Pearson's correlation coefficient was calculated along with the significance for this test. (3) Results: Correlations between SP-2 and SPM subscales ranged from r = 0.127 (p. 174) to r = 0.674 (p < 0.001). Correlations between sensory factors analyzing the same sensory systems ranged from r = 0.401 (p < 0.001) to r = 0.674 (p < 0.001) for body position/body awareness and hearing, respectively. (4) Conclusions: There is adequate convergent validity between the SPM and the SP-2 for the Spanish population in most sensory factors. The results support the use of both sensory questionnaires with the Spanish population.